The problems of the social functioning of 10 year old gifted boy with depressive episode - Masiak, Jolanta; Eugene, Andy (Current Problems of Psychiatry, 2011)
The family of the boy consists of both parents and two younger sisters. Because of the specificity of the father’s work the family lives from time to time in different countries. Both parents are Polish, but the family lives in America for good. The boy is a student of a local public school and is bilingual. The parents stress that the boy since early childhood was characterized by the emotional coldness, he tended to isolate from the peer group also he was not emotionally bounded to his sisters. Sometimes he was aggressive against them. He was also very serious and could not take part in the spontaneous games of other children. At the same time he differed from other children of his very high intellectual level and of interests that were far beyond of usual interests of his peers. It was noticed and stressed by his school teachers. He was interested mostly in the problems of science and also in politics. He felt comfortable discussing with adult people the mentioned problems. During last some months however his frame of mind was changed. He complained to parents that strange thoughts are coming threw his mind that he is a bad person and tendencies to hurt himself. At the same time he became more tensed and dysphoric in contact with his sisters.. The patient was treated by individual cognitive behavioral psychotherapy. He was also treated pharmacologically but in a very little part. Also the parents of the boy were educated concerning their relations with the boy based on the behavioral technics. After two months of the treatment the depressive symptoms disappeared. We discussed with the parents the strategy of long term upbringing and educational strategies (first of all the training of the successful functioning in the boys peer groups) also concerning eventual correction of his schizoid personality traits and as a result to better psychosocial adjustment and functioning. We also discussed his future educational plan according to his high intellectual level and his interests.